Principles of the execution of responsible objects auction principles - Syamsul; Moch Isnaeni; Endang Prasetyawati (Technium Social Sciences Journal, 2021)
This type of legal research in this study uses juridical-normative. Ratio Legis to Mortgage Certificates based on Article 14 of the Mortgage Law Number 4 of 1996, has met the legal requirements, because the creditor and debtor have made a Credit Agreement in which the Power of Attorney to impose Mortgage and Deed of Granting Mortgage, and Acknowledgment of Gross Debt Deed is made before a Notary Official / Land Deed Making Officer, as Article 10 in juncto with Article 14 of the Mortgage Law provides legal protection to the main creditor, because the object of the mortgage has been registered with the Land Office so that it has executive power over the object Mortgage right. Fiat Court executes mortgage object at the request of the creditor in which the debtor cannot sell the object as pledged voluntarily, the creditor requests the Chairman of the Court to request legal protection, and justice to the State Apparatus, on the Mortgage Certificate which already has the Executional Power of the Object of Rights dependents.